Weeds in human affairs in subSaharan Africa: implications for sustainable food production - Akobundu, I. (Cambridge University Press, 1991)
Sub-Saharan Africa (SSA) has the world's largest human population growth rate, some of its poorest soils, and a high incidence of crop pests. Weeds are the major pest in virtually all of the agro-ecological zones of SSA. Parasitic and perennial weeds dominate the savanna vegetation zones whereas rapidly growing annual weeds overwhelm crops in the forest vegetation zones. High weed pressure coupled with inefficient weed control practices have tied up a disproportionate percentage of SSA's economically active population in the primary task of food production and also have kept crop yields down. In the absence of organized weed research and professional training in weed science to meet the needs of the region, improved cultivars of virtually all crops fall prey to weeds, and available arable land becomes limited to that area that can be kept free of weeds. A preponderance of annual weeds in humid parts of SSA together with hard-to-kill perennial grasses and parasitic weeds in the subhumid and arid agro-ecological zones hamper crop production and frustrate farmers throughout the region. Sustainable food production in the region can be achieved by introducing improved weed management technologies and by addressing other food production constraints of the region.